2017
DOI: 10.1089/neu.2016.4636
|View full text |Cite
|
Sign up to set email alerts
|

Acute or Delayed Treatment with Anatabine Improves Spatial Memory and Reduces Pathological Sequelae at Late Time-Points after Repetitive Mild Traumatic Brain Injury

Abstract: (2017) Acute or delayed treatment with anatabine improves spatial memory and reduces pathological sequelae at late time-points after repetitive mild traumatic brain injury. Journal of Neurotrauma, 34(8), pp. 1676Neurotrauma, 34(8), pp. -1691Neurotrauma, 34(8), pp. . (doi:10.1089Neurotrauma, 34(8), pp. /neu.2016 This is the author's final accepted version.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.ht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Previously, we found that pharmacological inhibition of chronic microglial activation beginning 1month post-injury using either mGluR5 agonists or delayed aerobic exercise, reduced neurodegeneration and improves long-term motor and cognitive recovery (Byrnes et al, 2012;Piao et al, 2013). Thus, these, and other pre-clinical studies (Ferguson et al, 2017), provide evidence for an expanded therapeutic window for neuroprotection by targeting chronic post-traumatic neuroinflammatory responses.…”
Section: Discussionmentioning
confidence: 76%
“…Previously, we found that pharmacological inhibition of chronic microglial activation beginning 1month post-injury using either mGluR5 agonists or delayed aerobic exercise, reduced neurodegeneration and improves long-term motor and cognitive recovery (Byrnes et al, 2012;Piao et al, 2013). Thus, these, and other pre-clinical studies (Ferguson et al, 2017), provide evidence for an expanded therapeutic window for neuroprotection by targeting chronic post-traumatic neuroinflammatory responses.…”
Section: Discussionmentioning
confidence: 76%
“…Both interventions significantly reduced NOX2 expression in chronically activated microglia. These, and other preclinical studies (Ferguson et al, 2017), provide additional evidence for an expanded therapeutic window for TBI by targeting chronic posttraumatic neuroinflammatory responses.…”
Section: Discussionmentioning
confidence: 84%
“…Racemic anatabine was marketed as an herbal supplement called Anatabloc by Rock Creek Pharmaceuticals. Several studies supported by this company have shown that anatabine, in addition to its anti-inflammatory actions, has procognitive [40][41][42][43], neuro-protective [44], immune disease modulating [45,46], and smoking cessation actions. Anatabine partially substitutes for nicotine in drug discrimination behavioral assays but does not have the addictive potency of nicotine [47,48].…”
Section: Discussionmentioning
confidence: 99%